(untitled) (International Journal of Engineering and Computer Science, 2016)
Traditional routing metrics designed for wireless networks are application-agnostic. In this paper, we consider a wireless network where the application flows consist of video traffic. From a user perspective, reducing the level of video distortion is critical. Popular link-quality-based routing metrics do not account for dependence across the links of a path; as a result, they can cause video flows to converge onto a few paths that cause high video distortion. To account for the evolution of the video frame loss process, we construct an analytical framework .The framework allows us to formulate a routing policy for minimizing distortion, based on which we design a protocol for routing video traffic. We find via simulations and test bed experiments that our protocol is efficient in reducing video distortion and minimizing the user experience degradation.